Konsep Jiwa Yang Tenang dalam Surat Al Fajr 27-30 (Perspektif Bimbingan Konseling Islam) - widodo, Anton; Rohman, Fathur (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2019)
AbstrackÂ As has been explained in the Qur'an that there are several levels in the human soul which is better known as the level of anger and lust for lawamah and lust muthmainnah. Q.Susuf verse 53 has explained that there is a lust that always invites evil or evil deeds. Furthermore lust lawwamah has been explained in al-Qu'an surah al-Qiyamah verse 2. In the letter explains that he is a lust that resides in the human soul and it is he who always invites to maintain the wholeness as the most perfect human figure of God. The mutmainah lust has clearly been interpreted in QS al-Fajr verse 27, which most people interpret as lust that always invites goodness. On this basis this paper was born with the focus of his study of the meaning of the muthmainnah soul in the Koran surah al-fajr verses 27-30 and its implementation in mental healthThis paper illustrates that kosep al-nafs al-muthmainnah (quiet soul) is the concept of the soul who is a believer, as well as a soul who is devoted to Allah SWT and that the Yaqin is always clean (holy) from impulses. On the four basic piety, faith, holiness and belief will bring the concept of a calm soul and change the mindset of humans in the face of failure. In order for each individual to be able to live in peace the individual needs Islamic guidance and counseling to achieve a calm, harmonious life free from lust of anger so that they can build mental health so they can live in a balanced and peaceful way.Â Keywoard: Quiet Soul Concept, Surat Al Fajr 27-30, Islamic Counseling Guidance